Conveyorized implementation of aswm image filter on PLD - Vasylchenkov, Oleg; Liberg, Igor; Mozhaiev, Mykhailo; Salnikov, Dmytro (PC Technology Center, 2021)
The object of research is the adaptive switching weighted median image filter (ASWM) algorithm. This algorithm is one of the most effective in the field of impulse noise suppression. The computational complexity and algorithmic features of this adaptive nonlinear filter make it impossible to implement a filter that works in real time on modern PLD microcircuits. The most problematic areas of the algorithm are the weight coefficient estimation cycle, which has no limit on the number of iterations and contains a large number of division operations. This does not allow implementing the filter on PLDs with a sufficiently effective method. In the course of the research, the programming model of the filter in Python was used. The performance of the algorithm was assessed using the Peak Signal-to-Noise Ratio (PSNR) and Structural Similarity Index Measure (SSIM) metrics.Modeling made it possible to find out empirically the number of iterations of the cycle for estimating the weight coefficients at different levels of noise density and to estimate the effect of artificial limitation of the maximum number of iterations on the filter performance. Regardless of the intensity of the noise impact, the algorithm performs less than 40 iterations of the evaluation cycle. Let’s also simulate the operation of the algorithm with different variants of the division module implementation. The paper considers the main of them and offers the most optimal in terms of the ratio of accuracy/hardware costs for implementation. Thus, a modified algorithm was proposed that does not have these disadvantages.Thanks to modifications of the algorithm, it is possible to implement a pipelined ASWM image filter on modern PLDs. The filter is synthesized for the main families of Intel PLDs. The implementation, which is not inferior in terms of SSIM and PSNR metrics to the original algorithm, requires less than 65,000 FPGA logical cells and allows filtering of monochrome images with FullHD resolution at 48 frames/s at a clock frequency of 100 MHz.

Об’єктом дослідження є алгоритм адаптивного перемикання зваженого медіанного фільтра зображення (ASWM). Цей алгоритм є одним з найефективніших у сфері придушення імпульсних перешкод. Обчислювальна складність і алгоритмічні особливості цього адаптивного нелінійного фільтра унеможливлюють реалізацію фільтра, який працює в режимі реального часу на сучасних мікросхемах PLD. Найбільш проблемними ділянками алгоритму є цикл оцінки вагового коефіцієнта, який не має обмеження на кількість ітерацій і містить велику кількість операцій ділення. Це не дозволяє реалізувати фільтр на PLD досить ефективним методом. У ході дослідження була використана модель програмування фільтра на мові Python. Ефективність алгоритму оцінювалася за допомогою показників пікового відношення сигнал-шум (PSNR) і показника структурної подібності (SSIM). Моделювання дозволило емпірично з’ясувати кількість ітерацій циклу для оцінки вагових коефіцієнтів при різних рівнях щільності шуму та оцінити вплив штучного обмеження максимальної кількості ітерацій на продуктивність фільтра. Незалежно від інтенсивності шумового впливу, алгоритм виконує менше 40 ітерацій циклу оцінки. Також змоделюємо роботу алгоритму з різними варіантами реалізації модуля ділення. У роботі розглянуто основні з них і запропоновано найбільш оптимальні за співвідношенням точність/апаратні витрати на реалізацію. Таким чином, був запропонований модифікований алгоритм, який не має цих недоліків. Завдяки модифікаціям алгоритму можна реалізувати конвеєрний фільтр зображення ASWM на сучасних PLD. Фільтр синтезований для основних сімейств Intel PLD. Реалізація, яка за показниками SSIM і PSNR не поступається оригінальному алгоритму, вимагає менше 65 000 логічних комірок FPGA і дозволяє фільтрувати монохромні зображення з роздільною здатністю FullHD з частотою 48 кадрів/с на тактовій частоті 100 МГц.
Keywords: adaptive filter; nonlinear filter; median filter; impulse noise; Peak Signal-to-Noise Ratio; Structural Similarity Index Measure; адаптивний фільтр; нелінійний фільтр; медіанний фільтр; імпульсний шум; вимірювання індексу структурної подібності; пікове відношення сигнал/шум